Analisis Kekuatan Pembuktian Akta Notaris yang Menimbulkan Sengketa Perdata Tinjauan Yuridis dalam Perkara No.165/PDT/2017/PT.MTR - Wahyu Mustariyanto; Krisno Jatmiko; Della Zaskia (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
A notary is a state-appointed public official vested with the duty and authority to draw up deeds. Pursuant to Article 1 point 1 of Law No. 2 of 2014, which amends Law No. 30 of 2004 on the Position of Notary, a notary is characterized as a public official empowered to prepare authentic deeds and endowed with additional authorities as stipulated by this law or other relevant legislation. In carrying out their duties, notaries have a moral responsibility towards their profession. Paul F. Camanisch stated that the profession is a moral community that shares the same ideals and values. This professional group has guidelines known as the Code of Professional Ethics. Violations of the notary's position can result in responsibility for the person carrying out the profession, both administratively and in civil compensation. Furthermore, notaries can be subject to criminal responsibility if they violate the Criminal Code in carrying out their duties and can be held accountable for actions taken in making Authentic Deeds that are not in accordance with the law.